Shakespeare’s Glocal Moorings: Transculturation in Two 2001 Celluloid Adaptations of Othello - Dhee Sankar; Semanti Nandi; Prasun Roy; Mercy Hembrom; Ayantika Bhaskar (HyperCultura, 2025)
Abstract: This article examines two film adaptations of Shakespeare’s Othello released in 2001, Geoffrey Sax's telefilm Othello and Tim Blake Nelson's O, from the perspective of Fernando Ortiz’s concept of transculturation, focusing on how ideas about race, gender and sexuality are translated from Shakespeare's text with its own historical situatedness, and transformed in two contemporary—coeval but contrasting—adaptations of it, one British and one American. The Early Modern category of “Moor” is adapted and expressed in these millennial productions in terms of the inter-Atlantic slave trade, because the violence and hybridity associated with it has made it a template for the transculturation of interracial relations in general and Othello in particular. The films allude to contemporary events to illustrate or re-interpret Shakespeare’s plot, including events of race-related violence such as the O. J. Simpson murder case, and of teenage violence like the Columbine High School massacre. The white homoerotic gaze on Othello’s black body is underscored in both films, and the counterparts of Iago perceive the counterparts of Othello as attractive alter-egos rather than enemies. I argue that the transculturation of race in the two films establishes Shakespeare’s Othello as a text with “glocal” cultural capital.